Model for Developing a Career Decision-Making Program - Winkles, Elizabeth J.; Johnson, Richard H. (Canadian Journal of Counselling and Psychotherapy, 2012)
This article describes the process used by a high school counselor to design career decision-making activities, field-test the activities, and use the field-test results to determine the most effective career decision-making program.